Hubungan Dukungan Sosial Dengan Stress Akademik Pada Mahasiswa Tingkat Akhir FKM di Universitas Islam Negeri Sumatera Utara: Indonesia - Salianto Salianto; Dita Wahyuni; Leoni Safitri Harianja; Lilis Karlina Boangmanalu; Salwa Radha Hera (Journal of Innovative and Creativity, 2025)
Academic stress is a widespread issue faced by students in their final year, as they grapple with academic expectations and requirements that surpass their ability to manage them. This research intends to investigate the connection between social support and academic stress among final-year students at the Faculty of Public Health, Universitas Islam Negeri Sumatera Utara. The study utilized a correlational quantitative framework with simple random sampling, including a total of 31 participants. Both academic stress and social support were assessed using Likert scales, and the data were processed through Spearman's correlation test. The findings demonstrated a moderate and statistically significant positive relationship between social support and academic stress (ρ = 0. 472, p = 0. 007), suggesting that increased social support relates to decreased levels of academic stress. These results align with the buffering theory, which posits that social support serves as a safeguard against stress. The practical implications highlight the necessity of enhancing academic mentoring programs and fostering social connections to mitigate academic stress in final-year students.